2019
DOI: 10.1101/626986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of bulk phosphatidylcholine compositions in human plasma using side-chain resolving lipidomics

Abstract: Running title: Composition of phosphatidylcholine sums in human plasmaAbbreviations: CV, coefficient of variation; conc., concentration; mGWAS, genome-wide association study with metabolic traits, MWAS, metabolome-wide association study, OGTT, oral glucose tolerance test; OLTT, oral lipid tolerance test; PC, phosphatidylcholine; pv, p-value; R, rest that consists of the totality of nonmeasured single PCs, SD, standard deviation 3 Abstract Kit-based assays, such as AbsoluteIDQ TM p150, are widely used in large … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…This labeling bases on the assumption that evennumbered fatty acids and lower degrees of desaturation are more common than odd-numbered fatty acids or very high degrees of desaturation. Common violations of these assumptions and observable mixed molecular compositions of measured PCs in human blood have been discussed recently in more detail (Quell et al, 2019). The assessed biologically relevant ratios include e.g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This labeling bases on the assumption that evennumbered fatty acids and lower degrees of desaturation are more common than odd-numbered fatty acids or very high degrees of desaturation. Common violations of these assumptions and observable mixed molecular compositions of measured PCs in human blood have been discussed recently in more detail (Quell et al, 2019). The assessed biologically relevant ratios include e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Quell et al recently showed that blood PC aa C36:6 measured in healthy young men mainly comprises a derivative of DHA, a fatty acid with 22 carbons and 6 double bonds (C22:6). Quell et al found PCaas that contain DHA as one, and tetradecanoic acid as the second fatty acid chain (PC 14:0_22:6) account for the major part (~88%) of measured PC aa C36:6 concentrations (Quell et al, 2019). They also suggested the second PCae that was higher in natural bodybuilders (PC ae C38:0) to be a DHA derivative.…”
Section: Natural Bodybuilders Have Higher Levels Of Two Docosahexaenoic Acid Derivatives Which May Originate From Supplemented Fish Oilsmentioning
confidence: 98%
See 2 more Smart Citations